ORAL CANCER: LYMPHO DISSECTION AT CN0 AND CN+ - Sh. I. Musin (Креативная хирургия и онкология)
High risk of regional metastasis of oral cancerrequires specialtactics keeping this cohort of patients . Neck dissection is an opportunity to conduct an adequate assessment of tumor process by N and also preventive / therapeutic effect on lymph flow path. In the study the results of treatment of 33 patients with oral cancer were analyzed. All patients underwent surgery for primary tumor and lymph drainage pathways . When cN0 25 lymphadenectomy was performed and histologically identified metastases in 6 patients with cN + passed 8 lymphadenectomy . In cancer of the oral cavity with cN+ and cN0 the dissection of levels I-IV is shown.